The Effect of Education on Self-Management and Stroke Prevention Behavior on Recurrence - Nur Aini; Erma Wahyu Mashfufa; Lilis Setyowati; Ollyvia Freeska Dwi Marta (Jurnal Multidisiplin Madani, 2022)
This study aimed to determine the provision of self-management education interventions to reduce recurrence in stroke patients. Method: research design experimental with intact group comparison design. The number of samples of 60 people was calculated using G power software, taken by purposive sampling technique, 29 intervention groups and 31 control groups. The research was conducted in poly stroke RSU Muhammadiyah Malang. The instrument used the Stroke Self-Management Questionnaire (SSMQ) for stroke prevention behavior. Chi-square and the Mann-Whitney test analyzed data. The statistical tests obtained a p-value for self-management behavior, and recurrence was not significant, while on stroke prevention behavior obtained a p-value of 0.034 < 0.05. Self-management educational interventions give patients the ability to control behavior and emotional responses so that patients can prevent stroke.